PENGUJIAN TRADE OFF THEORY PADA STRUKTUR MODAL PERUSAHAAN DALAM INDEKS SAHAM KOMPAS100 - Dewi Setiawati, AA Sg Mira; Putra, I Wayan (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
The research purpose to determine the effect of fixed tangible assets, profitability, firm size and growth of the company on the capital structure of companies included in the stock index KOMPAS100 listed on the Indonesian Stock Exchange 2011-2013. Purposive sampling method is used as a method of selecting a sample in order to obtain as much as 197 observations. Multiple linear regression analysis was used to analyze secondary data in this research. The results show the independent variable of fixed tangible assets, profitability, firm size, and firm growth effects the capital structure. Partially fixed tangible assets, firm size and firm growth positively significant affect the capital structure of listed companies in the stock index KOMPAS100. Variables profitability negatively significant effect the company's capital structure in the index KOMPAS100.
Keywords: fixed tangible assets, profitability, firm size, firm growth, capital structure